Enzyme activity and thermostability of a non-specific nuclease from Yersinia enterocolitica subsp. palearctica by site-directed mutagenesis - Yu Zhang; Zhen-Hua Li; Wei Zheng; Zhen-Xing Tang; Zhi-Liang Zhang; Lu-E Shi (Electronic Journal of Biotechnology, 2016)
Background: To identify the critical amino acid residues that contribute to the high enzyme activity and good thermostability of Yersinia enterocolitica subsp. palearctica (Y. NSN), 15 mutants of Y. NSN were obtained by site-directed mutagenesis in this study. And their enzyme activity and thermostability were assayed. Effect of several factors on the enzyme activity and thermostability of Y. NSN, was also investigated. Results: The results showed that the I203F and D264E mutants retained approximately 75% and 70% enzyme activity, respectively, compared to the wild-type enzyme. In addition to the I203F and D264E mutants, the mutant E202A had an obvious influence on the thermostability of Y. NSN. According to the analysis of enzyme activity and thermostability of Y. NSN, we found that Glu202, Ile203 and Asp264 might be the key residues for its high enzyme activity and good thermostability. Conclusions: Among all factors affecting enzyme activity and thermostability of Y. NSN, they failed to explain the experimental results well. One reason might be that the enzyme activity and thermostability of Y. NSN were affected not only by a single factor but also by the entire environment.